Polynomial logistic distribution associated with a cubic polynomial. Issue 14 (18th July 2017) - Aksoy, Ümit; Ostrovska, Sofiya; Özban, Ahmet Yaşar
ABSTRACT: Let P ( x ) be a polynomial monotone increasing on ( − ∞, +∞). The probability distribution possessing the distribution function is called the polynomial logistic distribution with associated polynomial P . This has recently been introduced by Koutras et al., who have also demonstrated its importance for modeling financial data. In this article, the properties of the polynomial logistic distribution with an associated polynomial of degree 3 have been investigated in detail. An example of polynomial logistic distribution describing daily exchange rate fluctuations for the US dollar versus the Turkish lira is provided.